Validity and reliability of the Indonesian Version of HIV-KQ-18 in assessing public knowledge about HIV/AIDS in the special region of Yogyakarta - Muh. Deni Kurniawan; Bustanul Arifin; M. Rifqi Rokhman; Dyah Aryani Perwitasari (Universitas Ahmad Dahlan, 2022)
An assessment of public knowledge about HIV/AIDS is necessary for the development of educational strategies and materials. A valid and reliable instrument is needed to obtain comparable assessment of public knowledge about HIV/AIDS from time to time. This research study aims to determine the validity and reliability of the Indonesian version of HIV-KQ-18 in assessing public knowledge about HIV/AIDS in the Special Region of Yogyakarta. This research study used a cross-sectional design with the inclusion criteria being people living in Yogyakarta who were at least 18 years old and the exclusion criteria being respondents who did not fill out the instrument completely and did not fill out duplicate forms from the same respondent. The instrument was analyzed using product-moment correlation and known-group validity, while its reliability was tested using Kuder-Richardson Formula 20 (KR20). The total number of respondents as the subjects in this research study was 305. The results of the validity test of the HIV-KQ-18 obtained an r-xy value from 0.177-.564, greater than r-table (0.112), and the HIV-KQ-18 instrument exhibited high reliability with a KR20 value of 0.763. The test of known-groups validity showed that there were significant differences in all groups tested, except for the group based on age. The HIV-KQ-18 is a valid and reliable instrument and it can be used to assess public knowledge about HIV/AIDS in the Special Region of Yogyakarta.